2021
DOI: 10.1007/s40843-021-1765-x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of large positive and negative magnetoresistance in Cr2Si2Te6 ferromagnetic semiconductor

Abstract: Magnetoresistance (MR) phenomenon couples the electron transport with magnetic field, which has been at the forefront of condensed matter physics and materials science. Large-MR behaviors are of particularly importance for magnetic sensor and information memory applications, and their scarcity has aroused intensive research. Moreover, due to the different physical origins, combination of large positive and negative MR (pMR and nMR) in one single compound has rarely been reported. In present work, we achieved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The CST bulk crystal results will be discussed rst. The EDS analysis spectrum and average chemical ratio (Cr: Si: Te = 18: 21: 60) of the platelet indicates that the content of Cr is slightly smaller than in previous reports 27,28 . Some Cr atoms are replaced by Si or Te, but the stoichiometry is near ideal for CST.…”
Section: Resultscontrasting
confidence: 55%
See 3 more Smart Citations
“…The CST bulk crystal results will be discussed rst. The EDS analysis spectrum and average chemical ratio (Cr: Si: Te = 18: 21: 60) of the platelet indicates that the content of Cr is slightly smaller than in previous reports 27,28 . Some Cr atoms are replaced by Si or Te, but the stoichiometry is near ideal for CST.…”
Section: Resultscontrasting
confidence: 55%
“…In thick CST akes (thickness more than 100 nm), the MR ratio increases with increasing magnetic eld and maintains a positive value. Although the ferromagnetic interaction and long-range ferromagnetic ordering in CST normally give NMR behavior, the total magnetoresistance effect always has other effects involved including orbit scattering, electron-electron correlation, and so on 27 . It indicates that even below T c there is still more than one effect contributing to the resistivity change.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the coexistence of charge and spin degrees of freedom in the diluted magnetic semiconductors, tremendous attention has been aroused in semiconductor spintronics. [1][2][3][4] As a promising wide-bandgap material that has been studied for a long time for various applications, including solar-blind detectors and high-frequency power devices, 5,6 very recently gallium oxide (Ga 2 O 3 ) has attracted much interest for its potentials in spintronic applications. [7][8][9][10] It is found that the ferromagnetism (FM) in Ga 2 O 3 can be realized by doping with various metallic elements, such as Fe, 11 Ni, 12 Cr, 13 Sn, 14 and Mn.…”
Section: Introductionmentioning
confidence: 99%